Participatory development of a care line for workers with Repetitive Strain Injury - Amélia Romana Almeida Torres; Ivana Cristina Holanda Cunha Barreto; Izabelle Mont´Alverne Napoleão Albuquerque; Valéria Bastos Gomes (Rev Rene)
Objective: to build an integral care line for workers with repetitive strain injuries. Methods:action-research with actions of the care line were developed in four workshops with the participation of 32 professionals, managers and users of primary, secondary and tertiary healthcare. Actions which obtained 80.0% agreement of the participants were included in the care line. Results: the Family Health Strategy was defined as the main gateway, coordinating and organizing the care through surveillance of workers’ health in its territory. As a secondary gateway, in urgent cases, referral hospitals were cited. The specialized care network was responsible for diagnosis, treatment and rehabilitation of referred cases. Conclusion: the care line developed by the action-research allowed the visualization of a flow to attention to workers and can be a reference for other municipalities.